Islamic influence on the architecture of the Malay world - Mohd Nawawi, Norwina (2009)
It is a lecture to a architecture students from Crete University for “Beyond the Boundaries of the West. Journeys to Spatial Conception of the East” Course. The lecture explains what is Islam and Islamic Architecture, what is Malay traditional architecture and how Islam come about to the South East Asian region and minimally influence the built environment we inherit today. This was the first time, the Greek students were exposed to South East Asian architecture through a live-skype presentation real time.